2015
DOI: 10.1186/s12939-015-0237-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between socioeconomic status/income and prevalence of diabetes and associated conditions: A cross-sectional population-based study in Saskatchewan, Canada

Abstract: IntroductionThe role that socioeconomic status/income play in accounting for the increased prevalence of type 2 diabetes has not been sufficiently studied in Canada. The primary purpose of the present study was to determine the unadjusted and adjusted effect of income on type 2 diabetes. The secondary purpose was to determine the adjusted effect of income on diabetes associated conditions such as high blood pressure and being overweight or obese, and its main behavioral factor of physical inactivity.MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
66
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 12 publications
9
66
1
3
Order By: Relevance
“…32,33 We also found that subjects with higher SII score had lower levels of physical activity (ß = -0.066, p<0.05). In agreement with our findings, Bird and colleagues 27 found that participants with lower income had higher levels of physical inactivity. This finding could relate to fewer and less safe environments, and/or lack of infrastructure (sidewalks and parks) that would decrease the practice of leisure physical activities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…32,33 We also found that subjects with higher SII score had lower levels of physical activity (ß = -0.066, p<0.05). In agreement with our findings, Bird and colleagues 27 found that participants with lower income had higher levels of physical inactivity. This finding could relate to fewer and less safe environments, and/or lack of infrastructure (sidewalks and parks) that would decrease the practice of leisure physical activities.…”
Section: Discussionsupporting
confidence: 93%
“…The relation between DM2 and socioeconomic inequalities observed in the present study has been reported in other populations previously. [24][25][26][27] For example, in a representative sample of the European population, Espelt and colleagues 24 found that women with a lower socioeconomic position (characterized by low education, low income, and low socioeconomic status) had 2.2 (95%CI: 1.9-2.7) higher prevalence ratio of DM2, while for men it was 1.6 (95%CI: 1.4-1.9). In this sense, multiple possible mechanisms have been described in the relation between socioeconomic inequalities and health.…”
Section: Discussionmentioning
confidence: 99%
“…A study to determine the effect of income on type 2 diabetes showed that after controlling for age, having a household income of $29,999 per year was associated with the type 2 diabetes prevalence (28). In addition, DM was regarded as a health problem in middle-aged living in low or medium developed countries, and elderlies living in high developed countries.…”
mentioning
confidence: 99%
“…Socio‐economic status (SES) is associated with the presence of Type 2 diabetes internationally . A thorough understanding of the relationship between SES and Type 2 diabetes is necessary to inform the development of population‐level preventive strategies, so that public health interventions can be tailored appropriately for different SES groups.…”
Section: Introductionmentioning
confidence: 99%
“…SES is a complex construct, with no ‘gold standard’ measurement . As a consequence, several different indicators have been developed to measure SES, including participants’ income, education or occupation . Different SES indicators can present different information on participants’ socio‐economic positions within their societies .…”
Section: Introductionmentioning
confidence: 99%